2013
DOI: 10.1021/tx300282k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 4-Hydroxy-1-(3-pyridyl)-1-butanone (HPB)-Releasing DNA Adducts in Human Exfoliated Oral Mucosa Cells by Liquid Chromatography–Electrospray Ionization–Tandem Mass Spectrometry

Abstract: Quantitation of DNA adducts could provide critical information on the relationship between exposure to tobacco smoke and cancer risk in smokers. In this study, we developed a robust and sensitive liquid chromatography-tandem mass spectrometry method for the analysis of 4-hydroxy-1-(3-pyridyl)-1-butanone (HPB1)-releasing DNA adducts in human oral cells, a non-invasive source of DNA for biomarker studies. Isolated DNA undergoes acid hydrolysis, after which samples are purified by solid-phase extraction and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 30 publications
4
70
0
Order By: Relevance
“…To achieve detection limits in the low fmol to amol range (1 per 10 8 –1 per 10 9 nucleotides) as required for our in vivo studies, we employed nanoLC/ESI + -HRMS 3 methodology on an Orbitrap Velos mass spectrometer. We and others have recently reported the use of high resolution mass spectrometry for DNA adduct analysis in complex samples and have shown that it dramatically reduces the matrix background, leading to greatly improved signal to noise ratios [37, 45, 46]. …”
Section: Resultsmentioning
confidence: 99%
“…To achieve detection limits in the low fmol to amol range (1 per 10 8 –1 per 10 9 nucleotides) as required for our in vivo studies, we employed nanoLC/ESI + -HRMS 3 methodology on an Orbitrap Velos mass spectrometer. We and others have recently reported the use of high resolution mass spectrometry for DNA adduct analysis in complex samples and have shown that it dramatically reduces the matrix background, leading to greatly improved signal to noise ratios [37, 45, 46]. …”
Section: Resultsmentioning
confidence: 99%
“…Once activated, NNN leads to formation of pyridyloxobutyl (POB)-DNA adducts [40]. Under strong acid hydrolysis conditions, the majority of POB-DNA adducts decompose to release 4-hydroxy-1-(3-pyridyl)-1-butanone (HPB) [4143]. In vitro and laboratory animal studies have demonstrated the importance of HPB-releasing adducts in NNK- and NNN-induced carcinogenesis [32,44].…”
Section: Tobacco Carcinogensmentioning
confidence: 99%
“…The use of high-resolution MS for the analysis of DNA adducts in complex samples could dramatically reduce the matrix background, leading to greatly improved signal-to-noise (s/n) ratios. 197,216 Likewise, the MS n scan mode also affords better s/n ratio owing to its high specificity, especially when there are co-eluting isobaric interferences. Meanwhile, the method allows for unambiguous identification of analytes of interest as detailed structural information is obtained from additional fragmentation pathways.…”
Section: Quantitative Analysis Of Dna Adductsmentioning
confidence: 99%
“…7 Quantitative analysis of 4-HPB-releasing DNA adducts uncovered these adducts as another robust biomarker to indicate the individual susceptibility to tobacco-induced cancers in humans. 216 …”
Section: Quantitative Analysis Of Dna Adductsmentioning
confidence: 99%